2020
DOI: 10.1002/ejp.1620
|View full text |Cite
|
Sign up to set email alerts
|

Sifting the wheat from the chaff? Evidence for the existence of an asymmetric fibromyalgia phenotype

Abstract: BackgroundThe different phenotypic presentations of fibromyalgia (FM) have been infrequently studied and may have diagnostic and therapeutic implications. The aim of this study was to explore differences between FM patients with classical symmetric (s‐FM) presentation and FM patients with marked asymmetric (a‐FM) pain.MethodsWe performed two consecutive cross‐sectional studies on FM patients and matched healthy volunteers (HV). FM patients were divided into a‐FM (and s‐FM groups according to their score of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…95.7% of participants with fibromyalgia and 86.6% of pain-free controls were women [one study did not indicate the proportion of men and women ( 57 )]. Fourteen studies out of the 19 reported a mean pain intensity rating, either at the moment of the participation [ n = 10; ( 24 , 27 , 31 , 34 , 36 , 37 , 57 60 )] or within the last month prior [ n = 4; ( 30 , 33 , 35 , 61 )]. In nine studies, including five in the meta-analysis ( 32 , 57 , 59 , 61 , 62 ), individuals with fibromyalgia were instructed to stop taking their medication prior to their participation ( 27 , 30 , 32 , 33 , 57 , 59 , 61 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…95.7% of participants with fibromyalgia and 86.6% of pain-free controls were women [one study did not indicate the proportion of men and women ( 57 )]. Fourteen studies out of the 19 reported a mean pain intensity rating, either at the moment of the participation [ n = 10; ( 24 , 27 , 31 , 34 , 36 , 37 , 57 60 )] or within the last month prior [ n = 4; ( 30 , 33 , 35 , 61 )]. In nine studies, including five in the meta-analysis ( 32 , 57 , 59 , 61 , 62 ), individuals with fibromyalgia were instructed to stop taking their medication prior to their participation ( 27 , 30 , 32 , 33 , 57 , 59 , 61 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TDT was assessed with Von Frey filaments in all studies except one ( 60 ) in which unspecified nylon filaments were used. For the TPT, five studies involved pinprick stimulators ( 27 , 28 , 30 , 32 , 35 , 36 , 61 ), five involved Von Frey filaments ( 34 , 37 , 57 , 62 , 63 ), one involved unspecified nylon filaments ( 60 ) and one involved disposable needles ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tests performed were already extensively used (Cury et al., 2016; Kaziyama et al., 2020; Lopes et al., 2018). Briefly, stimuli were applied on the thenar eminence of the asymptomatic limb (i.e.…”
Section: Methodsmentioning
confidence: 99%